Case Studies in Extending the School Day in Latin America - Alfaro, Pablo; Holland, Peter (World Bank, Washington, DC, 2015)
The case study in extending the school day in Latin America includes the following countries in this paper: Argentina, Rio Negro, Chile, Brazil, Sao Paulo, Uruguay, Argentina, Mendoza, El Salvador, and Mexico.